Approaches between exegesis by tradition and exegesis by opinion and their effect on glorifying Allah - Al-Hiti , Omar Abdul SattarRukan (International Journal of Psychosocial Rehabilitation, 2020)
There is no doubt that the glorification of God every Muslim and Muslim should be described with attributes of perfection and majesty, and to refrain from everything that is not befitting of His Majesty, glory be to Him, and it is known that the Holy One.